Application of The Simplex Method and Digital Literacy in Profit Optimization Problems Taufik Tempe - Ambarsari, Ida Fitriana; Hasanah, Nur; Astindari, Tri; Sari, Fadhila Kartika; Masruro, Anisyah Aulia (Universitas Wiralodra, 2024)
Resource allocation in the production process are important things that need to be considered to achieve optimal production levels. Production optimization problems are still an obstacle for most businesses operating in the food sector. One of them is the “Taufik Tempe” business which produces tempeh in three different sizes, namely large, medium, and small. The business owner finds it difficult to determine the amount of production according to market demand and minimize production costs for maximum profits. This research aims to solve the profit optimization problem of “Taufik Tempe” with appropriate production allocation to achieve maximum profits. The method used is the method of data collection and data analysis. Data collection methods include field studies (observations and interviews) and literature review. Meanwhile, data analysis uses the simplex method and uses MATLAB software. Data analysis techniques using observation and interviews. Meanwhile, the research results show that the maximum profit per month obtained is Rp 750.000,00 by focusing on producing only large-sized tempeh. Furthermore, by using MATLAB software the same results are obtained as using the simplex method but with a simple, effective and efficient algorithm, ofcourse with precise results and the use of this software aims to avoid calculation errors.